Roles of Eph-Ephrin Signaling in the Eye Lens Cataractogenesis, Biomechanics, and Homeostasis - Murugan, Subashree; Cheng, Catherine (Frontiers in Cell and Developmental Biology, 2022)
The eye lens is responsible for fine focusing of light onto the retina, and its function relies on tissue transparency and biomechanical properties. Recent studies have demonstrated the importance of Eph-ephrin signaling for the maintenance of life-long lens homeostasis. The binding of Eph receptor tyrosine kinases to ephrin ligands leads to a bidirectional signaling pathway that controls many cellular processes. In particular, dysfunction of the receptor EphA2 or the ligand ephrin-A5 lead to a variety of congenital and age-related cataracts, defined as any opacity in the lens, in human patients. In addition, a wealth of animal studies reveal the unique and overlapping functions of EphA2 and ephrin-A5 in lens cell shape, cell organization and patterning, and overall tissue optical and biomechanical properties. Significant differences in lens phenotypes of mouse models with disrupted EphA2 or ephrin-A5 signaling indicate that genetic modifiers likely affect cataract phenotypes and progression, suggesting a possible reason for the variability of human cataracts due to Eph-ephrin dysfunction. This review summarizes the roles of EphA2 and ephrin-A5 in the lens and suggests future avenues of study.